EKSISTENSI FILSAFAT EKONOMI SYARIAH DALAM PELAKSANAAN BANK SYARIAH DI INDONESIA - Yasnimawati; Syukri iska (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This article aims to analyze the philosophy of Islamic economics which is the basis for the operation of Islamic banking. The research approach is carried out through the analysis of literature related to philosophy in the context of Islamic banking. The philosophy of Islamic economics forms a solid foundation for Islamic banking. The values ​​of ethics, justice, and avoidance of usury are the main foundations in developing financial products that are in accordance with Islamic principles. Although implementation challenges exist, Islamic banking continues to play a role in combining religious teachings with modern needs in the fields of economics and finance.